Management control systems in response to social and environmental risk in large Nordic companies - Natalia Semenova (International Journal of Corporate Social Responsibility (JCSR), 2021)
This empirical study investigates the relationships between management control systems and social and environmental risks. Building on Simons' Levers of Control conceptual framework, this study proposes that companies facing social and environmental risks will enhance the quality of their management control systems by integrating social and environmental elements into management control systems in order to manage the related risks. The study uses a longitudinal dataset of the 1179 largest listed Nordic companies for the period 2014-2018. The multivariate regression confirms a negative relationship between the social and environmental integration and social and environmental risks. The results indicate that the social and environmental integrated performance measurement system and strategy implementation are not congruent with the social and environmental risks that the companies face. Nordic companies have not adopted the social and environmental integrated measurement system and strategy in response to social and environmental risks. When the number of social and environmental incidents increase and companies meet high levels of social and environmental risks, their management control systems do not match the related risks. Such social and environmental integration should be improved in order to prevent wider negative implications of the incidents on the natural environment and society in large.
Keywords: 650; Corporate responsibility; Management control systems; Sustainability; Social and environmental risk; Levers of control; Management accounting